Single-Layer Metasurface-Based Wideband Circularly Polarized Antenna Using CMA With RCS Reduction - Zhendong Ding; Junrui Yu; Jianyin Cao; Hao Wang; Dan Zhang; Michael Yan-Wah Chia; null Nasimuddin (International Journal of Antennas and Propagation)
A low-profile wideband circularly polarized (CP), single-layer antenna with low radar cross section (RCS) reduction based on staggered elliptical metasurface using characteristic mode analysis (CMA) is presented. The staggered arrangement of the elliptical metasurface has a 90° relationship, ensuring the generation of circular polarization, and their modes of fusion can achieve RCS reduction by CMA. The defective ground shows that the difference in characteristic angle (CA) between the two pairs of modes is about 90°. The measured results show that the antenna has a 40.6% (5.5 GHz–8.3 GHz) impedance bandwidth (IBW), a 26.2% (6.3 GHz–8.2 GHz) 3-dB axial ratio bandwidth (ARBW), and a peak gain of 5.1 dBic is achieved at 6.3 GHz, and with a large RCS reduces across the frequency range from 2.0 GHz to 22.0 GHz (166.7%). Monostatic RCS reduction of more than 5 dBsm is achieved within the frequency range from 4.6 GHz to 22.0 GHz (130.8%).